1940
DOI: 10.1084/jem.71.5.661
|View full text |Cite
|
Sign up to set email alerts
|

The Inactivation of the Virus of Epidemic Influenza by Soaps

Abstract: The capacity of certain fatty acids at pH 7.5 to inactivate the virus of epidemic influenza has been demonstrated. Most effective of these are oleic, linolic, and linolenic acids. Studies were made of such variables as pH, rate of inactivation, and ratios of reactant concentrations, using oleic acid as a prototype of the effective acids. Attempts to recover active virus from inactive mixtures by decrease in pH, dialysis, dilution, or addition of calcium chloride solution to inactivated virus hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

1952
1952
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 18 publications
0
30
0
1
Order By: Relevance
“…The sedimentation analyses performed on inactivated virions showed that 6 virions inactivated by a potent unsaturated alcohol (y-linolenyl alcohol) or monoglyceride (monoolein) remain nearly intact but have lost the ability to attach to host cells, whereas phage PM2 is nearly totally disrupted by monopalmitolein. The measured temperature dependencies of inactivation of these phages may be related to the ability of the compound to partition from its micellar aggregates (16) into the viral lipid bilayer, thereby causing limited disruption of the extemal (p6 envelope but much greater disruption, and hence virus disassembly, of the internal PM2 lipid bilayer. These sedimentation analyses results are similar to those we previously found for the inactivation of (p6 (19) and PM2 (3) by BHT (at higher concentrations than those used in the experiments reported here).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sedimentation analyses performed on inactivated virions showed that 6 virions inactivated by a potent unsaturated alcohol (y-linolenyl alcohol) or monoglyceride (monoolein) remain nearly intact but have lost the ability to attach to host cells, whereas phage PM2 is nearly totally disrupted by monopalmitolein. The measured temperature dependencies of inactivation of these phages may be related to the ability of the compound to partition from its micellar aggregates (16) into the viral lipid bilayer, thereby causing limited disruption of the extemal (p6 envelope but much greater disruption, and hence virus disassembly, of the internal PM2 lipid bilayer. These sedimentation analyses results are similar to those we previously found for the inactivation of (p6 (19) and PM2 (3) by BHT (at higher concentrations than those used in the experiments reported here).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported 30 years ago that an unsaturated fatty acid (oleic acid, 18:1, A9 cis) inactivates influenza type A virions (16). Very little work on the potential antiviral activity of low concentrations of fatty acids and other hydrocarbon derivatives has been done until recently.…”
mentioning
confidence: 99%
“…In subsequent years, the antifungal and bactericidal properties of fatty acids have been extensively investigated (5,12,22). Other reports point to the inactivation of virus by various soaps (24), as well as to the antitumor activity of fatty acids (25). In the past, certain generalizations were made concerning the activity of fatty acids on cells and microorganisms; however, owing to the impurity of the compounds used, the limited number of organisms tested in the same laboratory, or both, interpretation of structure-function relationships is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Similar behaviour is exhibited by a number of other viruses. Under certain conditions of time and temperature, vaccinia (Beard, Finkelstein & Wyckoff, 1938), influenza (Stock & Francis, 1940), mumps (We& Beard, Sharp & Beard, 1948) and Lansing poliomyelitis virus (Bachrach & Schwerdt, 1952) all retained their infectivity when exposed to wide ranges of hydrogen-ion concentration. On the other hand, Alexander (1935) showed the extreme sensitivity of horsesickness virus which, while stable to a range of values above pH 5.96, underwent immediate inactivation when exposed to pH values even slightly less than this value.…”
Section: Discussionmentioning
confidence: 99%